The effect of fixational eye movements on fixation identification with a dispersion-based fixation detection algorithm - Pieter Blignaut; Tanya Beelders (Bern Open Publishing, 2009)
Gaze data of 31 participants of a memory recall experiment was analyzed and the I-DT dispersion based algorithm of Salvucci and Goldberg (2000) was used to identify fixations. It was found that individuals differ considerably with regard to the stability of eye gaze and that fixational eye movements affect the accuracy of fixation identification and the optimum dispersion threshold. It was also found that fixation radius and the distance between the points in a fixation that are the furthest apart are the most reliable metrics for a dispersion-based fixation identification algorithm. Finally, it is argued that the correct setting of dispersion threshold is of utmost importance, especially if the participants are not homogeneous with regard to gaze stability.